Integrated bioprocess to boost cellulosic bioethanol titers and yields - Xu, Youjie (Kansas State University, 2018)
Among potential alternative liquid fuels, bioethanol is the widest utilized transportation fuels and mainly made from grains. Cellulosic biofuels provide environmental benefits not available from grain or sugar-based biofuels and are considered as a solid foundation to meet transportation fuels needs in a low-carbon economy, albeit with electrified vehicles and other technical advances. The objective of this research was to develop and optimize various bioprocessing units to boost cellulosic bioethanol titers and yields in order to accelerate the commercialization of cellulosic bioethanol production. The results showed high-solids biomass bioconversion (12%, w/v) was inefficient in the laboratory rotary shaker. However, a horizontal reactor with good mixing was effective for high solids loading (20%, w/v), yielding 75 g/L of glucose. To achieve the minimal economical ethanol distillation requirement of 40 g/L, integrated bioprocesses were conducted to boost ethanol titers and yields through co-fermentation of starchy grain and cellulosic biomass. The maximum ethanol concentration (68.7 g/L) was achieved at the corn flour and hydrothermal-treated corn stover ratio of 12:12 using raw starch granular enzyme with the ethanol yield of 86.0%. Co-fermentation of starchy substrate with hydrolysate liquor from saccharified biomass was able to significantly enhance ethanol concentration and reduce energy cost for distillation without sacrificing ethanol yields. These results indicated integration of first and second generation ethanol production could significantly accelerate the commercialization of cellulosic biofuel production. Novel technology, modified simultaneous saccharification and fermentation, was firstly established to enhance ethanol titers and yields, which achieved high ethanol titers of 72.3 g/L at high biomass loadings of 30% (w/v) with 70.0% ethanol yield.
Keywords: Biomass; Biofuels; Pretreatment; Fermentation; Ethanol